Educação linguística crítica de aprendizes de inglês : problematizações e desestabilizações - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
This qualitative-interpretative study discusses the philosophical and epistemological assumptions of critical language education and investigates the possibility of performing it through the problematization of social and political themes in an extension course designed for this purpose. In more specific terms, it investigates how the process of the participants’ and of the researcher’s critical language education took place during the course; identifies and discusses the participants' perceptions of their critical language education process throughout the course; problematizes the participants’ interventions in the choice of themes, in the mediations, and in the critical moments which occurred during the course. The empirical material of this study was gathered in the last semester of 2015, by means of an identification questionnaire, audio and video recordings of six ‘meetings’, interviews, a ‘roda de conversa’, and the participants’ final narratives. The research field was an extension course held at Universidade Estadual de Goiás, titled Speak up - Write down! Critical speaking and writing, which aimed at discussing critical themes that were relevant and emerged from the participants’ suggestions. In order to discuss the participants' perceptions about the course, we used theoretical reflections of critical pedagogy and of those who problematize it, of critical perspectives in language education, and of (critical) applied linguistics. After problematizing the empirical material, we realized that the participants had the opportunity to discuss themes that meant something to them, which, in our view, contributed to their agency and commitment to their critical language education process. In addition, the debates also allowed the researcher to take part in his critical language education and have his regime of truths strained and moved to other possibilities of interpretation of the topics addressed. We understand, therefore, that the problematization of themes suggested by the participants allowed them as well as the researcher to perceive the diversity of positions on the most varied subjects. To finish with, we believe these discussions were responsible for estimating the value and singularity of each participant’s opinion, once these opinions allowed them and the researcher to (re)consider their attitudes in the world, with the world and with themselves.
Keywords: Educação linguística crítica; Aprendizes de inglês; Curso de extensão; Problematização de temas; Critical languages education; English students; Extension course; Problematization of themes; CIENCIAS HUMANAS::EDUCACAO; LETRAS::LINGUAS CLASSICAS; LINGUISTICA, LETRAS E ARTES::LINGUISTICA